2019
DOI: 10.1038/s41372-019-0471-1
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death in preterm neonates (<33 weeks) born in tertiary care hospitals in India: analysis of three large prospective multicentric cohorts

Abstract: Objective To estimate the direct causes of mortality among preterm neonates <33 weeks' gestation by examining three large multicentric, hospital-based datasets in India. Method Three prospective hospital-based datasets: National Neonatal Perinatal Database (NNPD) of India, Delhi Neonatal Infection Study (DeNIS) cohort, and Goat Lung Surfactant Extract (GLSE)-Plus cohort were analyzed to study the causes of death among preterm neonates of less than 33 weeks' gestation admitted to the participating tertiary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
1
24
2
1
Order By: Relevance
“…The higher incidence of sepsis causing neonatal deaths were consistent with two recent studies from India reporting up to 41% of deaths due to sepsis in VLBW infants. 20,21 Antenatal care practices may differ, including frequency of prenatal care visits, gestational age at maternal referral, and antibiotics administered to mothers with preterm rupture of membranes or preterm labor. Postnatal care practices differ as well, including empirical antibiotics chosen for early or late onset sepsis for preterm infants with risk factors, central line maintenance, and infection control prac-tices.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence of sepsis causing neonatal deaths were consistent with two recent studies from India reporting up to 41% of deaths due to sepsis in VLBW infants. 20,21 Antenatal care practices may differ, including frequency of prenatal care visits, gestational age at maternal referral, and antibiotics administered to mothers with preterm rupture of membranes or preterm labor. Postnatal care practices differ as well, including empirical antibiotics chosen for early or late onset sepsis for preterm infants with risk factors, central line maintenance, and infection control prac-tices.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study from Ethiopia shows RDS to be the most prevalent cause of preterm death followed by sepsis (11) . In a large prospective Indian study using three hospital-based data sets from National Neonatal Perinatal Database (NNPD), Delhi Neonatal Infection Study (DeNIS), and Goat Lung Surfactant Extract (GLSE)-plus cohorts, K Jain et al in 2019 (12) analyzed that among preterm neonates of less than 33 weeks, sepsis is an important direct cause of death attributing to 20-40% of mortality, prematurity related complications were the causes of death in 40-50% cases and perinatal events accounted for only 9-12% deaths in this gestational group.…”
Section: Discussionmentioning
confidence: 99%
“…22 cohort and Goat Lung Surfactant Extract (GLSE)-Plus cohort) and concluded that 20-40% of preterm neonates less than 33 weeks gestation admitted to Indian NICUs were died of sepsis. 23 Their conclusion was that in verbal autopsy based analysis would have classified all deaths in preterm infants <33 weeks gestation to be directly related to prematurity related complications. Whereas analysis of hospital-based medical certification attributed prematurity related complications as a cause of mortality in only 40-50% of babies.…”
Section: Discussionmentioning
confidence: 99%